A validation methodology and application of 3D garment simulation software to determine the distribution of air layers in garments during walking. (March 2018) - Mert, Emel; Psikuta, Agnes; Arévalo, Marlène; Charbonnier, Caecilia; Luible-Bär, Christiane; Bueno, Marie-Ange; Rossi, René M.
Highlights: Agreement between air gap of 3D scanning and simulation dependent on body region. The movement of the body has an effect on the air gap thickness and contact area. Cycles of movement were reflected in cyclic change in air gap thickness. Abstract: The methods to determine air gap thickness and contact area are limited for stationary position of the manikin. In this study, 3D garment simulation software was quantitatively validated by comparing these parameters obtained from this tool with the ones obtained from accurate 3D scanning method to assess the capability of 3D garment simulation software. Moreover, for the first time, these parameters were calculated for garments on walking male avatar wearing t-shirt and sweatpants. The agreement between two methods were within a range of 23 mm and 65%, and 10 mm and 45% for the air gap thickness and contact area of upper and lower body garments, respectively. Furthermore, the adapted post-processing method could discriminate the differences in the observed parameters over the body regions and among the phases of the movement. The introduced post-processing method can be used to improve 3D garment software for the determination of the regional parameters.